DYSTOCIA DUE TO OBLIQUE VENTRO-TRANSVERSE PRESENTATION IN A MARE - A CASE STUDY - NAKHASHI, H C; PATEL, P B; FARUQUIE, S; PANDEY, R; CHAUDHARY, S (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to oblique ventro-transverse presentation along with ankylosed body parts and its successful delivery by caesarian section has been reported in mare.